Models and Fictions in (Micro-)Economics - Philipp C. Wichardt (Lund University, School of Economics and Management, Department of Economics, 2014)
How can an argument that is based on assumptions known to be false deliver any insightful conclusions let alone be used for policy recommendations? Over the years, a variety of concerns regarding (micro-)economic modelling and its relevance for real life have been expressed along these lines. Adding to this methodological discussion, I take seriously the recurrent comparison of economic models with literary fiction (fables, metaphors, parables,...) and argue that many of the concerns expressed can be alleviated in a coherent picture if one adopts the fiction view of models proposed by Frigg (2010a,b). In particular, I argue how adopting such a view not only opens a way for meaningful comparisons of economic models with reality but also relieves the pressure on assumptions to be empirically verifiable. Moreover, the argument suggests a distinctive role for strong mathematical theories such as expected utility theory (setting limits to the fictional world to be imagined), the often extensive story telling in economic modelling (adapting the model to a context and suggesting comparisons with "reality") as well as for empirical studies putting economic modelling to the test (exploring properties of the real world and how they relate to properties of the fictional model-world). Thus, suggesting a coherent framework in which various aspects of the discussion can be accommodated, I hope to add some valuable structure to the ongoing debate about how to interpret (micro-)economic modelling.
Keywords: B40; B41; 330; Fictions; Modelling; Microeconomics; Story Telling